Decolonizing visualities: changing cultural paradigms, freeing ourselves from Western-centric epistemes. - Ka Zenzile, Mawande (Michaelis School of Fine Art, 2020)
In this study, I hope to challenge the absolute belief in academia, which assumes that the perception of reality or visualities; in terms of culture, nature, truth and so on, by definition should be understood according to the Western philosophical character and genealogy as developed from a positivist paradigm. It seems to me, that the dominant methodological frameworks as I know them now, tacitly follow this scientific, quantitative, material, mechanical, positivist paradigm that draws from Western philosophical development and positions, pervasively held as the only basis for knowledge production. In turn, this philosophical position delegitimises any other epistemologies or methodological frameworks from elsewhere. In many cases, the methods of teaching and assessing subscribe, impose and perpetuate these same protocols as the only recognised epistemological and methodological approaches for critical inquiry inside tertiary educational institutions. By far, fine art as a discipline has inherited this epistemological position. To define this field in the context of decolonisation (meaning the undoing of colonisation), it requires us to look beyond disciplinary knowledge. This research is primarily an epistemological critique; and does not simply seek to “Africanise” the study of art, but to condemn the pervasive institutionalised cultural dominance. To frame my discourse, I have adopted an anti-colonial perspective, and a qualitative method to help define this phenomenon through a wide range of techniques. These include grounded theory; propositional logic; case study, narrative inquiry and auto-ethnography as possible tool for collecting, coding and analysing of data.